Auditory feedback decreases timing variability for discontinuous and continuous motor tasks in autistic adults - Richard Williams, Nicole; Tremblay, Luc; Hurt-Thaut, Corene; Brian, Jessica; Kowaleski, Julia; Mertel, Kathrin; Shlüter, Sebastian; Thaut, Michael (Frontiers in Integrative Neuroscience, 2024)
Introduction Autistic individuals demonstrate greater variability and timing error in their motor performance than neurotypical individuals, likely due at least in part to atypical cerebellar characteristics and connectivity. These motor difficulties may differentially affect discrete as opposed to continuous movements in autistic individuals. Augmented auditory feedback has the potential to aid motor timing and variability due to intact auditory-motor pathways in autism and high sensitivity in autistic individuals to auditory stimuli. Methods This experiment investigated whether there were differences in timing accuracy and variability in autistic adults as a function of task (discontinuous vs. continuous movements) and condition (augmented auditory feedback vs. no auditory feedback) in a synchronization-continuation paradigm. Ten autistic young adults aged 17–27 years of age completed the within-subjects study that involved drawing circles at 800 milliseconds intervals on a touch screen. In the discontinuous task, participants traced a series of discrete circles and paused at the top of each circle for at least 60 milliseconds. In the continuous task, participants traced the circles without pausing. Participants traced circles in either a non-auditory condition, or an auditory condition in which they heard a tone each time that they completed a circle drawing. Results Participants had significantly better timing accuracy on the continuous timing task as opposed to the discontinuous task. Timing consistency was significantly higher for tasks performed with auditory feedback. Discussion This research reveals that motor difficulties in autistic individuals affect discrete timing tasks more than continuous tasks, and provides evidence that augmented auditory feedback may be able to mitigate some of the timing variability present in autistic persons’ movements. These results provide support for future investigation on the use of music-based therapies involving auditory feedback to address motor dysfunction in autistic individuals.